PR-технології в системі маркетингових комунікацій - Вертегел, Сергій Якович; Вертегел, Сергей Яковлевич; Vertehel, Serhii (My University, 2018)
UK: У статті розглянуто зв’язки з громадськістю як частини маркетингових комунікацій та ви-значення їх ефективності. Визначено сутність паблік рилейшнз та розглянуті діючі моделі. Також визначено характер українського рекламно-комунікаційного ринку та основні тренди розвитку PR. Виявлено залежність між зв’язками з громадськістю та маркетинговими комунікаціями. Запропоновано методи вимірювання результативності піар-технологій. EN: The essence of public relations is determined and the existing models are considered. Also, the nature of the Ukrainian advertising and communications market and the main trends of PR development are determined. De-pendence between public relations and marketing communications is revealed. The methods of measuring the effective-ness of PR-technologies are proposed. The market in Ukraine needs from enterprises to establish demand for its prod-ucts to establish constructive relations with customers and suppliers to work closely with the public. Achievement of this goal is possible with the use of such a tool of marketing communications as public relations. The purpose of this article is to study the essence of public relations as part of the marketing communications of the enterprise and determine their effectiveness. Public relations as one of the main elements of marketing communications in many respects predeter-mines the competitiveness of enterprises, playing a prominent role in the formation of a marketing strategy. The essence of PR is expressed in the form of 4 models of views and characteristics of this category. There are two approaches that determine the essence of PR - social and technological. The difficult question for marketers is how to determine the effectiveness of marketing communications. Depending on the organization's goals in marketing communications, eco-nomic efficiency and communicative effectiveness are distinguished. PR works with different audiences, using different technologies of influence. In each case, the effectiveness will be determined differently. PR helps to create the image of the company and increase its efficiency. Consequently, PR today is one of the most important components of marketing communications.
PR-technologies in the marketing communication system
Keywords: паблік рилейшнз; ефективність; маркетингові комунікації; оцінка; public relations; effectiveness; marketing communications; value